INTERNET-RESOURCES’ USE AS A FACTOR FOR STUDENTS’ INTELLECTUAL DEVELOPMENT - Dutkevych, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article highlights the results of a studentsʼ survey regarding the Internet resources using peculiarities in the interests of educational tasks’ achievement. It is shown that students’ intellectual development is both a condition (to ensure a student’s critical understanding of information from the Internet) and a result of effective Internet resources use by processing information, structuring it, distinguishing between reliable and unreliable.